BERBAGAI FAKTOR RISIKO TERHADAP KEJADIAN PREEKLAMPSIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS BANDA RAYA KOTA BANDA ACEH - Evi Dewi Yani; T.M Rafsanjani (Dian Nuswantoro Semarang, 2023)
The incidence of preeclampsia has increased, in 2020 there were 29 cases and increased to 32 cases in 2021, this is influenced by the mother with labor first ( primipara ), lack knowledge Mother about pre- eclampsia , age Mother pregnant at risk , ANC visits are not complete , and tiring work. This study aims to determine the various risk factors with the incident preeclampsia on Mother Pregnant in the Work Area Banda Raya Health Center. This research is descriptive analytic with case-control design. Data collection is done by interview. The population in this study were 60 mothers pregnant third trimester and the sample is determined by the total sample technique with a ratio of 1:1, namely 30 respondents who had preeclampsia and 30 who did not have preeclampsia. The statistical test used is the chi-square test. The results showed that parity was at risk 6.5 times (OR=6.571. p=0.001), ANC visits were at risk 5.5 times (OR=5.500. p = 0.002) and mother's work was at risk 4 times (OR=4.030. p=0.010) ) to events preeclampsia. The conclusion of this study is that parity, ANC visits, and work are risk factors for events preeclampsia on Mother Pregnant in the Work Area Banda Raya Health Center in 2021. Suggested to health workers is necessary more improved Again visit And counseling to Mother pregnant in order to knowledge Mother increase Good in prevent preeclampsia.Keywords: ANC Visit, Parity, Preeclampsia, Occupation.